Eksplorasi Peran Guru dalam Pemilihan Metode Pembelajaran yang Sesuai dengan Karakteristik Siswa - Khalisatun Husna; Tiara Lubis; Fikri Hamdi Siregar; Abdul Fattah Nasution (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The learning method is a systematic and orderly process carried out by teachers or educators in delivering material to their students. Through the learning method, it is expected that the teaching and learning process can run well. Thus, it is very important for an educator to know the methods in learning so that students feel more enthusiastic when participating in learning in the classroom. In addition, choosing the right method makes students not quickly feel bored or tired when participating in teaching and learning activities in the classroom. The purpose of writing this article is to find out how a teacher chooses a learning method. The method in this study is qualitative narrative, with data collected from the results of semi-structured interviews with a teacher. The results of this study indicate that there are 2 factors that a teacher can consider in choosing a learning method, namely internal and external factors. Internal factors include student characteristics, facilities and infrastructure, teacher experience and skills, and learning objectives. Then external factors include the curriculum and learning environment.